Moderate-intensity interval exercise but not high-intensity interval exercise improves the spatial memory of ovariectomized rats - Kaidah, Siti; Rauf, Saidah; Soesatyo, Marsetyawan HNE; Agustiningsih, Denny; Partadiredja, Ginus (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Physical exercise exerts beneficial effects on the spatial learning and memory. High-intensity interval exercise (HIIE) has been proposed as a time-efficient physical exercise regimen. On the other hand, there were evidences that HIIE increased oxidative stress biomarkers and reduced antioxidant capacity, which resulted in oxidative damage. The present study aimed to investigate the effects of high-intensity interval exercise and moderate-intensity interval exercise on oxidative stress biomarkers and oxidative enzymes activity in the hippocampus and the spatial memory of ovariectomized rats. A total of 16 female Sprague Dawley rats aged 12 weeks were randomly assigned into 4 groups, i.e. the sham-operated (SO), ovariectomized without exercise (O), ovariectomized with high-intensity interval exercise (HIIE), and ovariectomized with moderate-intensity interval exercise (MIIE) groups. Rats of the exercise groups (HIIE & MIIE groups) performed 6 sessions of interval exercise per week for 6 weeks. The spatial memory of rats was measured using the Morris water maze procedure. The malondialdehyde (MDA) levels and activity of catalase (Cat) as well as glutathione peroxidase (GPx) in hippocampus were determined using spectrophotometry method. The spatial learning and memory retention of the moderate-intensity interval exercise group was significantly better than that of the high-intensity interval exercise group. The GPx activity of MIIE group was higher than any other groups. The SO group had the lowest hippocampal MDA level and highest Cat activity among groups. Moderate-intensity interval exercise reduces the ovariectomy induced-oxidative stress in the hippocampus and improves spatial learning and memory retention of ovariectomized rats.